New and little-known crickets from Southern Guangxi, China (Orthoptera: Grylloidea: Gryllidae: Phalangopsidae; Trigonidiidae) - Zhang, Ling; Shen, Chu-Ze; Tian, Di; Liu, Yun-Fei; Li, Kai; He, Zhu-Qing (Zootaxa, 2019)
The crickets from Southern Guangxi, China have been investigated from 2017–2019. Teleogryllus (Brachyteleogryllus) commodus and Lissotrachelus ferrugineonotatus are first reported from Guangxi. Two new species, Polionemobius marblus He sp. nov. and Ornebius panda He sp. nov., are described along with their calling songs. The COI genes of above species and Cacoplistes brevisparamerus, Gorochovius trinervus are provided. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).